Pengaruh Kinerja Keuangan dan Struktur Modal Terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi: Studi pada Perusahaan Manufaktur Sub Sektor Food and Beverage di BEI Periode 2021-2024 - Ni Kadek Pande Febriyanti; I.G.A Desy Arlita; Ketut Tanti Kustina; Putu Pande R. Aprilyani Dewi (Ikatan Da'i Indonesia, 2025)
This study aims to examine and determine the effect of financial performance and capital structure on firm value with firm size as a moderating variable. The independent variable of financial performance in this study is measured by Return on Assets (ROA), while capital structure is measured by Debt to Equity Ratio (DER). The dependent variable of firm value is measured by Price to Book Value (PBV), and the moderating variable of firm size is measured by the Natural Logarithm (Ln) of Total Assets. This research employs a quantitative approach with purposive sampling method using secondary data based on predetermined criteria. A total of 256 observations were obtained from 19 food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. The data analysis technique used is Moderated Regression Analysis (MRA). The results of this study indicate that financial performance and capital structure have a significant positive effect on firm value. Firm size is able to moderate the effect of financial performance on firm value, while firm size is unable to moderate the effect of capital structure on firm value.